Au nanoparticle homogeneously decorated C@TiO2 for enhanced visible-light-driven photocatalytic activity. Issue 126 (8th December 2015) - Zheng, Yan-Zhen; Xu, Yan-Yan; Fang, Hua-Bin; Wang, Yuan; Tao, Xia
Abstract : A Au–C@TiO2 photocatalyst shows excellent visible-light response characteristics and promotes charge carrier separation and transport efficiency. Abstract : Highly efficient visible-light-driven photocatalysts i.e. Au–C@TiO2 have been prepared by a facile and reproducible impregnation–precipitation process. The structure and properties of the photocatalysts were characterized by HRTEM, EDS elemental mapping, XPS, UV-vis and PL techniques. It is found that 6 nm-sized Au nanoparticles are homogeneously decorated within amorphous C@TiO2 . The amorphous carbon shell has been demonstrated to be able to extend the photoresponse range of C@TiO2 . The plasmonic Au nanoparticles loaded within C@TiO2 greatly improve visible light absorption, charge separation efficiency and transfer of photogenerated electrons and holes. As a result, in the degradation experiments of RhB and 1-NP, the visible-light photocatalytic activity of Au-decorated C@TiO2 can be greatly enhanced by Au nanoparticles and a carbon shell. We envision that such a high efficiency Au–C@TiO2 photocatalyst prepared via a facile impregnation–precipitation method may be a promising candidate for organic pollutant degradation.